(untitled) (Journal of Advanced Veterinary Research, 2012)
Foot and mouth disease (FMD) is considered one of the enzootic animal diseases in Saudi Arabia. During the period 2005-2009, large numbers of FMD type O outbreaks were reported and related to FMDV ME-SA Pan Asia II topotype. FMD type A virus was only detected in December 2005. Its phylogenetic analysis confirmed that this type A virus was a member of the ASIA topotype. Our results of molecular-biological studies revealed that FMDV type O Manisa that present in the current vaccine formula appears to have only a moderate match against some isolates of the currently circulating FMDV type O PanAsia strain while FMD type A virus was most closely related to the Iranian A/Iran /2005. So, the authors recommend using a tetravalent vaccine containing type O FMDV PanAsia topotype, type A Iran 2005, Asia1 and Sat2 for FMD prevention in the large Saudi Arabian dairy farms. In addition to, bivalent vaccine containing type O FMDV PanAsia topotype and type A Iran 2005 for the routine vaccination campaigns all over the country.